Electrode Stack Studies of a Vanadium Redox Flow Batteries - Mohd Rusllim, Mohamed (2014)
Vanadium redox flow battery (V-RFB) emerges as newly developing energy storage technology; some are under field testing and demonstration stage, but information on construction, electrode stack, electrolyte preparation, overall systems under study, etc. are still limited. This paper concisely reviews of redox flow batteries, its components and design considerations. Experimental performance characterisations at different electrode stack compartments from a 25 - 100 cm2 laboratory, unit cell, all-vanadium redox flow battery (VRFB) are presented. The results are compared to lithium-ion and conventional lead-acid in estimating the size and performance of a V-RFB, suitable for a series hybrid electric vehicle (HEy). Suggestion for system improvement is highlighted.